Analisis Penegakan Hukum Terhadap Tindak Pidana Umum Yang Dilakukan Oleh Prajurit TNI - Nabila Adifia Azzahra; Irwan Triadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This study aims to determine law enforcement in Indonesia regarding general criminal offenses committed by TNI soldiers. The law enforcement is analyzed in order to know the difference between general crimes and military crimes. This research uses normative legal analysis research. By looking at library materials (secondary data), normative legal research is carried out which includes legal principles, legal systematics, comparative law, and legal history.   This research provides results that a military member who commits a military and general criminal offense will be subject to confinement and additional sanctions. This is explained in Law No. 34 of 2004 which has also been explained in Article 65 paragraph (2) stipulates that soldiers are subject to military judicial power in the event of a violation of military criminal law and are subject to general judicial power in the event of a violation of general criminal law regulated by law.